REACH Story of Change: Participatory water resource management - REACH (University of Oxford, 2023)
A para-hydrology initiative in two regions of Ethiopia trained citizen scientists to collect quantitative data on rural hydrological systems. Citizen science hydrometeorological data has been successfully used in several peer-reviewed studies to predict and assess the impact of sustainable land management interventions. The research has informed approaches to participatory monitoring in two major sustainable land management programmes run by Ethiopia’s Ministry of Agriculture & Natural Resources. A gender-sensitive approach is required to address the current barriers to women’s involvement in citizen science and water management decisions.